CHALLENGE-BASED ASSESSMENTS IN A GAMIFIED LEARNING ENVIRONMENT: A CASE STUDY ON LINGUISTICS STUDENTS - Dexter Sigan, John; Chuah, Kee Man; Keezrawati, Mujan Yusuf (2020)
The increasing call for students to be equipped with 21st-century skills has prompted many academic programmes in tertiary learning institutions to revise their core focus particularly in their learning delivery and assessments. This study reports on the incorporation of challenge-based assessments in the Language and Computing course offered in a Linguistics undergraduate programme in a Malaysian university. In particular, the key tenets of challenge-based assessments are embedded within a gamified learning environment, in which the students are assessed progressively through a series of challenges. The course was run for 14 weeks with 68 students. By the end of the course, the students were required to evaluate their overall experience through a questionnaire. The findings showed that the novel use of challenge-based assessments has sustained students’ interest in the course. Moreover, observable behavioural changes were also apparent such as the increase in attendance rate and active discussions in face-to-face classes. The students’ perceptions regarding the whole course were notably positive with high ratings given to the constructs covered in the questionnaire. Ultimately, this case study provided valuable insights on how gamified challenge-based assessments can enhance students’ engagement and deep learning.